2016
DOI: 10.1080/14737167.2016.1179116
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of child-specific utilities in NICE appraisals for paediatric indications: rise of the economic orphans?

Abstract: Children are not mini-adults, and thus require studies to be conducted in the population of interest to inform decisions about their care. The paucity of such studies for clinical efficacy lead them to be termed 'therapeutic orphans'. Following the introduction of the 'fourth hurdle' of reimbursement approval on the basis of cost-utility analysis, utility data is now a key requirement for patients to access treatments in England and many other countries. This special report considers whether a paucity of utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A meta-analysis of childhood health utilities by Kwon et al 17 also found that although child-specific instruments are applied quite frequently, the most commonly used indirect valuation method was the Health Utilities Index Mark 3. The same observation was made by Montgomery and Kusel, 18 who found that in most published National Institute for Health and Care Excellence appraisals concerning child populations, adult utilities were used to inform the decision model. Nevertheless, as they also argue, children are not small adults and we cannot assume that their preferences are the same as in the adult population.…”
Section: Introductionmentioning
confidence: 56%
“…A meta-analysis of childhood health utilities by Kwon et al 17 also found that although child-specific instruments are applied quite frequently, the most commonly used indirect valuation method was the Health Utilities Index Mark 3. The same observation was made by Montgomery and Kusel, 18 who found that in most published National Institute for Health and Care Excellence appraisals concerning child populations, adult utilities were used to inform the decision model. Nevertheless, as they also argue, children are not small adults and we cannot assume that their preferences are the same as in the adult population.…”
Section: Introductionmentioning
confidence: 56%
“…A commentary in 2016 briefly reviewed the approaches to generate utility values in child populations in NICE technology appraisals over time 21 and 'found that most had used adult utilities to inform the model, due to the unavailability of suitable child derived utilities; furthermore, it was clear that there was no trend away from this over time' (p. 349). However, this statement was supported using only three illustrative case studies.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the HTA and reimbursement agencies reported uncertainties in utility values and questioned the added value of nusinersen in SMA subtypes, in type 0, type IV, and even type III SMA. In the past, methodologies to determine utility values have been criticized for being ill-adapted to the needs of younger patients (Eiser and Morse, 2001;Matza et al, 2004;Prosser, 2009;Ungar, 2011;Lim et al, 2014;Montgomery and Kusel, 2016;Gissen et al, 2021). These shortcomings become more impactful considering the fact that 69.9% of rare diseases present themselves in a mainly young patient population, such as in the case of SMA (Nguengang Wakap et al, 2020).…”
Section: Barriers Towards the Economic Evaluation Of Nusinersenmentioning
confidence: 99%